The Relationship Between Personality Types and Sexual Dysfunction - Hosseini, Fatemeh; Beygi, Zahra; Yazdanpanahi, Zahra; Akbarzadeh, Marzieh (Current Women's Health Reviews, 2021)
Background: Sexual function is affected by various physiological and psychological factors. Individual differences and various personality types are effective in response to sexual function. Objective: The present study aimed to investigate the correlation between sexual function and personality types among the women referred to healthcare centers in Shiraz in 2014 till 2015. Methods: This cross-sectional, descriptive-analytical study was conducted on 514 women referred to healthcare centers in Shiraz. The study data were collected using a demographic information form, the Female Sexual Function Index (FSFI), and a NEO Personality Inventory. Written informed consent forms were also obtained from the participants. Afterward, the data were analysed through the SPSS software, version 19, using t-test, chi-square test, and Fisher’s exact test. Results: The results showed sexual desire disorder in 39% of the participants, sexual arousal disorder in 38.6%, orgasm disorder in 25.5%, and sexual pain in 33%. The results also indicated that sexual desire, arousal, and pain were significantly associated with extroversion and reversely related to neuroticism. Conclusions: The score of extroversion was higher in individuals without sexual dysfunction, while the score of neuroticism was higher among individuals with sexual dysfunction. Therefore, it is necessary to evaluate women’s personality types as a technique for the assessment of sexual dysfunction.
Keywords: women